Bioenergy and the city – What can urban forests contribute?. (1st March 2016) - Kraxner, F.; Aoki, K.; Kindermann, G.; Leduc, S.; Albrecht, F.; Liu, J.; Yamagata, Y.
Highlights: New methodology for analyzing sustainable urban biomass for bioenergy. Application to real-life case study – Vienna Woods Biosphere Reserve. Balancing tradeoffs between urban ecosystem services. Additional bioenergy potential from Viennese urban forest identified. Urban bioenergy contributes to urban energy resilience and emissions reductions. Abstract: Bioenergy plays an important role in mitigating dangerous climate change and will therefore most likely have to further expand substantially. With 50% of the global population living in urban areas, cities are transforming into hotspots for future sustainable energy systems in the context of a low-carbon society. Bioenergy feedstock from urban forests could contribute substantially to low-carbon energy supply, yet urban ecosystems also provide other services that have to be balanced against future energy needs. This study conducts a geo-spatial analysis of urban forests with respect to its potential of increasing feedstock production for urban bioenergy generation. At the same time, social and environmental constraints are considered and co-benefits discussed. In order to test the wider applicability of the methodology, the Vienna Woods Biosphere Reserve is chosen as a case study to determine the feedstock potential for local bioenergy provided to Viennese households. The theoretical biomass potential is modeled using biophysical growth and yield tables for individual tree species and then compared to the existing production area using GIS tools. Results show that the biomass use within the biosphere reserve can be increased by about 60% without violating any national or international law that protects multiple ecosystem services provided by the reserve, nor sustainability criteria of forest management. This indicates a high potential of peri-urban forest ecosystems to contribute to urban resilience – i.e. with respect to energy security and emissions reduction. The study concludes that urban forests require sensible management in order to minimize conflicts of multiple environmental, economic and social uses of the area.